Study of Effect of Salvianolic Acid B on Motor Function Recovery in Rats with Spinal Cord Injury. (18th March 2014) - Xun, Chong; Hu, Yang; Lu, Ming; Wang, Shouyu; Lv, Decheng
Abstract : In this study effect of salvianolic acid B was observed on motor function recovery of rats with spinal cord injury. 50 rats were selected and after inducing SCI their recovery under controlled conditions was studied using Sal B and PBS (as control). Both compounds were introduced intraperitoneally in respective groups of traumatic rats at the same time intervals for 28 days. It was observed that Sal B introduced at 5  mg/kg/day resulted in better motor function recovery. BBB score was recorded which increased significantly along with the reduction in cavity area observed by bright field microscopy of tissues, that is, from 1 to 10 and from 0.20 ± 0.05  mm 2 to 0.10 ± 0.03  mm 2, in Sal B treated group, respectively, compared to PBS group. Statistical analysis was carried out using SPSS software (SPSS, Chicago, IL, USA), values were expressed as mean ± SEM, and P value <0.01 was considered significant. Effect of Sal B on expression of NF-kB p65 and IkB α was studied and OD values of densitometry of western blots were taken. MPO activity was also studied. It was observed that treatment of Sal B significantly reduced the expression of both compounds in Sal B treated group as compared to control group after 28 days of treatment.